Optimal implantation depth and adherence to guidelines on permanent pacing to improve the results of transcatheter aortic valve replacement with the medtronic corevalve system - Petronio, Anna Sonia; Bekeredjian, Raffi (JACC Cardiovascular interventions, 2015)
The aim of the CoreValve prospective, international, post-market ADVANCE-II study was to define the rates of conduction disturbances and permanent pacemaker implantation (PPI) after transcatheter aortic valve replacement with the Medtronic CoreValve System (Minneapolis, Minnesota) using optimized implantation techniques and application of international guidelines on cardiac pacing. Conduction disturbances are a frequent complication of transcatheter aortic valve replacement. The rates of PPI in the published reports vary according to bioprosthesis type and the indications for PPI. The primary endpoint was the 30-day incidence of PPI with Class I/II indications when the Medtronic CoreValve System was implanted at an optimal depth (≤6 mm below the aortic annulus). The timing and resolution of all new-onset conduction disturbances were analyzed. A total of 194 patients were treated. The overall rate of PPI for Class I/II indications was 18.2%. An optimal depth was reached in 43.2% of patients, with a nonsignificantly lower incidence of PPI in patients with depths ≤6 mm, compared with those with deeper implants (13.3% vs. 21.1%; p = 0.14). In a paired analysis, new-onset left bundle branch block and first-degree atrioventricular block occurred in 45.4% and 39.0% of patients, respectively, and resolved spontaneously within 30 days in 43.2% and 73.9%, respectively. In patients with new PPI, the rate of intrinsic sinus rhythm increased from 25.9% at 7 days to 59.3% at 30 days (p = 0.004). Optimal Medtronic CoreValve System deployment and adherence to international guidelines on cardiac pacing are associated with a lower rate of new PPI after transcatheter aortic valve replacement, compared with results reported in previous studies. (CoreValve Advance-II Study: Prospective International Post-Market Study [ADVANCE II]; NCT01624870)